Using Integrated Enterprise Systems to Achieve Strategic Goals: A case study of a dual mode university - Smith, Alan (International Review of Research in Open and Distributed Learning, 2005)
Since 1999, the University of Southern Queensland has embarked on a range of initiatives designed to improve the infrastructure and systems used to support its widely ranging activities in teaching and learning and research and its expansion into new international markets. This has involved the careful selection and implementation of various enterprise systems, together with the use of horizontal process teams. The results of this approach are now being realized, with demonstrable improvements to many university services, together with significant cost efficiencies. This paper discusses the reasons for the changes, the processes used to drive the changes through the various university committee structures, and the outcomes of the implementation of the enterprise systems.